The Impact of Health-Related User Interface Sounds on Player Experience. (June 2017) - Robb, James; Garner, Tom; Collins, Karen; Nacke, Lennart E.
Background . Understanding howsound functions on informational and emotional levels withinvideo games is critical to understandingplayer experience of games.User interface sounds, such asplayer-character health, are a pivotal component of gameplay across many video game genres, yet have not been studied in detail. Method . To address this research gap in user interface sounds, we present two studies: The first study examines the impact of the presence or absence ofplayer-health sounds on player experience. The second study explores the impact of thetypes of sound used to indicate player health. We use mixed methods withqualitative andphysiological measures . Results . Our results reveal that despite the presence of visual cues, sound is still important togame design for conveying health-related information and that the type of sound affects player experience.